Organic Leaf Fertilizer Application to Increase Jabon Seedling Growth (Anthocephalus cadamba Roxb. Miq.) - Arum Sekar Wulandari; Sri Susanti (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2012)
Good seedlings have good genetic quality and physical appearance such high, diameter, age, fresh leaves, free from pests and diseases. One way to get good quality seedling throughs fertilizing. Research aims to know response of Jabon seedling growth which is given organic leaf fertilizer. Research is done in the greenhouse by using complete random design (RAL). Treatment which is given on jabon seedlings was granting organic leaf fertilizer, namely: fertilizer X, super-O, Saputra, and Agrobost. As control, jabon seedlings not given organic leaf fertilizer. The observed variables are the seedlings high, stem diameter, wet weight of shoots and roots, shoots and root dry weight ratio tops, roots, and root length. The results showed from 9 variables observed there are 7 variables that influence on growth of the jabon seedling, such as: high, diameter, heavy wet shoots and root dry weight, shoot and roots. The granting of organic leaf fertilizer Saputra gives a better growth than other treatments in terms of high growth that is 21.38 cm (nearly 15.34%), diameter is 3.59 mm (increase 36.59%), wet weight of shoots weighing nearly 18.78 g (increase 26.90%), heavy wet roots weighing is 7.74 g (increase 68.82%), dry weight of shoots is 3.13 g (nearly 93.17%) root dry weight, weighing 1.91 g (increase 117.16%). Seedling control and seedling treatment had NPA between 1.54-2.23. Seedlings jabon on all treatments have a long the same root, but it has a number of different roots. Jabon seedlings on all the treatments have a long the same root, but it has a number of different roots. The seeds are sprayed with organic leaf fertilizers have quality index value of seedings > 0.09, meaning seed jabon can survive if moved to the field.